2020
DOI: 10.1021/acsomega.0c00377
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Virgin Asphalt Binder Combined with High Percentages of RAP Binder Rejuvenated with Waste Vegetable Oil

Abstract: Waste cooking oils (WCOs) show promise as a rejuvenator for reclaimed asphalt pavement (RAP) binders. Their use helps to make RAP a renewable resource and to address environmental concerns related to WCO disposal. While studies suggest that 100% RAP for pavement is feasible, RAP will likely be combined with a virgin binder and aggregate incrementally in the field. In this study, the rheological properties of the virgin binder blended with a simulated RAP binder and 10% waste vegetable oil (WVO) as a rejuvenato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The Han curve, designed to forecast the compatibility of mixtures with distinct chemical structures and phases, uses viscoelastic parameters from oscillatory shearing flow states. , A Han curve positioned toward the lower right of the reference line suggests a predominant viscous component . The following abbreviation is used here: “RA” followed by the name of a rejuvenator indicates the rejuvenated asphalt binder produced by mixing P20 with the named rejuvenator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Han curve, designed to forecast the compatibility of mixtures with distinct chemical structures and phases, uses viscoelastic parameters from oscillatory shearing flow states. , A Han curve positioned toward the lower right of the reference line suggests a predominant viscous component . The following abbreviation is used here: “RA” followed by the name of a rejuvenator indicates the rejuvenated asphalt binder produced by mixing P20 with the named rejuvenator.…”
Section: Resultsmentioning
confidence: 99%
“…42,43 A Han curve positioned toward the lower right of the reference line suggests a predominant viscous component. 44 The following abbreviation is used here: "RA" followed by the name of a rejuvenator indicates the rejuvenated asphalt binder produced by mixing P20 with the named rejuvenator. As shown in Figure 12, the Han curves for RA-SO-I and RA-PO, situated at the lower right, demonstrate that the double logarithmic curves of G″ against G′ at diverse temperatures yield a continuous trajectory.…”
Section: Hanmentioning
confidence: 99%
“…Finally, the third category is post-consume oil wastes that include but are not limited to cooking oil/residues, waste auto engine oil/residues, cottonseed, and soybean oil residues [17,18]. Many studies have indicated that most of these materials could restore the balance lost after aging between asphaltene maltenes and aromatics by using different contents [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%